Islamic Finance in Ghana: Can MSMEs Benefit? - Abdul-Somed, Ibrahim; Yatoo, Nissar Ahmad; Yusif, Geofrey (Universitas Syiah Kuala, 2024)
Objective The purpose of this study is to examine the potential benefits of the implementation of Islamic Banking and Finance (IBF) in Ghana and opportunities for businesses using MSMEs as data source.Design/Methodology Primary data were obtained using questionnaires, where 400 questionnaires were distributed to MSMEs operators with a final sample of 308 respondents. The data collected were analyzed with SPSS 26.0 and the results were discussed.Results The findings reveal that MSMEs (businesses) are yearning for Islamic banking to reap several benefits such as alternative sources of funding, alternative source of savings, reduction of loan defaults and acceptance of Islamic banking among MSMEs. In addition, more males responded compared to females likewise majority of respondents are Muslims.Research limitations/implications majority of the respondents were Muslims though Islam is a minority religion in Ghana, hence may not reflect the views of the entire Ghanaian population.Novelty/Originality This study is the first of its kind in Ghana in terms of the data source and size of the sample used. This study is also a contribution to the limited literature of IBF in Ghana. The outcome of the study will guide government to design framework for IBF takeoff in Ghana.